The methylome of a human polar body reflects that of its sibling oocyte and its aberrance may indicate poor embryo development. Issue 2 (12th December 2020) - Yuan, Peng; Guo, Qianying; Guo, Hongshan; Lian, Ying; Zhai, Fan; Yan, Zhiqiang; Long, Chuan; Zhu, Ping; Tang, Fuchou; Qiao, Jie; Yan, Liying
Abstract: STUDY QUESTION: Is it possible to evaluate the methylome of individual oocytes to investigate the DNA methylome alterations in metaphase II (MII) oocytes with reduced embryo developmental potential? SUMMARY ANSWER: The DNA methylome of each human first polar body (PB1) closely mirrored that of its sibling MII oocyte; hypermethylated long interspersed nuclear element (LINE) and long terminal repeats (LTRs) and methylation aberrations in PB1 promoter regions may indicate poor embryo development. WHAT IS KNOWN ALREADY: The developmental potential of an embryo is determined by the oocyte's developmental competence, and the PB1 is a good substitute to examine the chromosomal status of the corresponding oocyte. However, DNA methylation, a key epigenetic modification, also regulates gene expression and embryo development. STUDY DESIGN, SIZE, DURATION: Twelve pairs of PB1s and sibling MII oocytes were biopsied and sequenced to compare their methylomes. To further investigate the methylome of PB1s and the potential epigenetic factors that may affect oocyte quality, MII oocytes (n = 74) were fertilized through ICSI, while PB1s were biopsied and profiled to measure DNA methylation. The corresponding embryos were further cultured to track their development potential. The oocytes and sperm samples used in this study were donated by healthy volunteers with signed informed consent. PARTICIPANTS/MATERIALS, SETTING, METHODS: Single-cell methylome sequencing was applied to obtain the DNA methylation profiles of PB1s and oocytes. The DNA methylome of PB1s was compared between the respective group of oocytes that progressed to blastocysts and the group of oocytes that failed to develop. DNA methylation levels of corresponding regions and differentially methylated regions were calculated using customized Perl and R scripts. RNA-seq data were downloaded from a previously published paper and reanalysed. MAIN RESULTS AND THE ROLE OF CHANCE: The results from PB1-MII oocyte pair validated that PB1 contains nearly the same methylome (average Pearson correlation is 0.92) with sibling MII oocyte. LINE and LTR expression increased markedly after fertilization. Moreover, the DNA methylation levels in LINE (including LINE1 and LINE2) and LTR were significantly higher in the PB1s of embryos that could not reach the blastocyst stage (Wilcoxon–Matt–Whitney test, P < 0.05). DNA methylation in PB1 promoters correlated negatively with gene expression of MII oocyte. Regarding the methylation status of the promoter regions, 66 genes were hypermethylated in the developmental arrested group, with their related functions (significantly enriched in several Gene Ontology terms) including transcription, positive regulation of adenylate cyclase activity, mitogen-activated protein kinase (MAPK) cascade and intracellular oestrogen receptor signalling pathway. LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: Data analysis performed in this study focused on the competence of human oocytes and compared them with maternal genetic and epigenetic profiles. Therefore, data regarding the potential regulatory roles of paternal genomes in embryo development are lacking. WIDER IMPLICATIONS OF THE FINDINGS: The results from PB1-oocyte pairs demonstrated that PB1s shared similar methylomes with their sibling oocytes. The selection of the good embryos for transfer should not only rely on morphology but also consider the DNA methylation of the corresponding PB1 and therefore MII oocyte. The application of early-stage analysis of PB1 offers an option for high-quality oocyte and embryo selection, which provides an additional tool for elective single embryo transfer in assisted reproduction. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by the National Key Research and Development Program of China (2018YFC1004003, 2017YFA0103801), the National Natural Science Foundation of China (81730038, 3187144, 81521002) and the Strategic Priority Research Program of the Chinese Academy of Sciences (XDA16020703). The authors have no conflicts of interest to declare.